Context Matters: Teaching Styles and Basic Psychological Needs Predicting Flourishing and Perfectionism in University Music Students - Herrera, Dora; Matos, Lennia; Gargurevich, Rafael; Lira, Benjamín; Valenzuela, Rafael (Frontiers in Psychology, 2021)
Professional musicians are expected to perform at a very high level of proficiency. Many times, this high standard is associated with perfectionism, which has been shown to prompt both adaptive and maladaptive motivational dynamics and outcomes among music students. The question about how perfectionism interplays with motivational dynamics in music students is still unanswered and research within this line is scarce, especially in Latin America. In the light of Self-Determination Theory (SDT), this cross-sectional study investigated the relationship between the perceptions of motivational context (teachers' motivating styles: autonomy supportive or controlling), basic psychological needs (satisfaction/frustration), perfectionism (adaptive/maladaptive), and flourishing in University music students from Lima, Peru (N = 149; mean age = 20.68, SD = 3.03; 71% men). We performed a path analysis testing a model in which motivational teaching styles predicted both, perfectionism and flourishing via need satisfaction and frustration. The model's fit indices were ideal [χ2 (7, N = 143) = 7.48, p = 0.300, CFI = 0.998, TLI = 0.992, RMSEA = 0.021, SRMR =0.040]. In this model, perceived autonomy supportive style predicted need satisfaction positively and need frustration negatively; perceived controlling teaching style did not predict need satisfaction nor frustration. In turn, need satisfaction positively predicted adaptive perfectionism (i.e., high standards) and flourishing; whereas, need frustration predicted maladaptive perfectionism (i.e., discrepancy). These results shed light on the relevance of perfectionism in the psychology of higher music education students. Lastly, we highlight the importance of autonomy support in fostering adaptive high standards and flourishing in music learning.